1980
DOI: 10.1002/jss.400130206
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution of binding protein dependent ribose transport in spheroplasts derived from a binding protein negative escherichia coli K12 mutant and from salmonella typhimurium

Abstract: Highly purified ribose-binding protein from Escherichia coli has been used to reconstitute binding-protein-dependent ribose transport in spheroplasts derived from a binding-protein-deficient mutant of E coli K12, and in spheroplasts derived from Salmonella typhimurium. The cross-species reconstitution was nearly as efficient as the reconstitution of the E coli strain from which the binding protein was derived. Antibody raised against the ribose binding protein completely prevented reconstitution, whereas it ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1981
1981
1988
1988

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Under these conditions, even proteins can be imported into the periplasm, as demonstrated by the reconstitution of maltose transport in the nonpolar deletion strain HS3018 (AmalE maW) by the addi-tion of maltose-binding protein (MBP). Previously, the reconstitution of binding protein-dependent transport had only been achieved by the addition of binding protein to spheroplasts or isolated membrane vesicles of mutant strains that were free of this protein (4,15,16,20,28). Reconstitution experiments with whole cells, which are much easier and highly reproducible, reflect a more natural situation.…”
mentioning
confidence: 99%
“…Under these conditions, even proteins can be imported into the periplasm, as demonstrated by the reconstitution of maltose transport in the nonpolar deletion strain HS3018 (AmalE maW) by the addi-tion of maltose-binding protein (MBP). Previously, the reconstitution of binding protein-dependent transport had only been achieved by the addition of binding protein to spheroplasts or isolated membrane vesicles of mutant strains that were free of this protein (4,15,16,20,28). Reconstitution experiments with whole cells, which are much easier and highly reproducible, reflect a more natural situation.…”
mentioning
confidence: 99%
“…Restoration of transport by binding protein was dependent upon the induction of the ribose transport system, but it did not require the metabolizing of ribose since reconstitution could be achieved with a strain that was constitutive for the transport system but lacked ribokinase. In recent work with this system, it was shown that binding protein dependent transport could be restored in spheroplasts from a mutant strain which is defective in the ribose binding protein but normal in the other component(s) of the ribose transport system (Robb et al, 1980).…”
Section: Discussionmentioning
confidence: 99%